A concise review on copper catalyzed synthesis of α-ketoamides - Amit Gautam; Biswa Ranjan Swain; Sonali B. Jethy; V. Ravichandiran; Sharada Prasanna Swain (Applied Catalysis O: Open)
The α-ketoamides are essential building blocks for the synthesis of β-lactams and oxazolidinones. As it contains multiple reactive centers, it could be a suitable starting material for following reactions such as Michael addition reaction, Pictet–Spengler reaction, Mannich, Stetter reaction etc. The familiar US FDA approved drug molecules bearing α-ketoamide moieties are boceprevir, telaprevir, fostemsavir, and varespladib. This review describes the research articles (since the year 2012) related copper-catalyzed α-ketoamides synthesis and mechanism of those reactions. Copper-catalyzed synthesis of α-ketoamides from aryl methyl ketones, aryl acetic acids, alkynes, aryl acetaldehydes, α-keto acids, α-azido ketones, and 1,3-diketo compounds have been discussed.